The Association Between Tei Index And Severity Of Coronary Artery Disease In Patients With Unstable Angina - Akram Shariati; Rogayeh Afsar Gharebagh; Alireza Rostamzadeh; Nazanin Sadeghifar; Nazila Pashaei; Reza Hajizadeh (مجله علمی دانشگاه علوم پزشکی کردستان)
Background and aim: Cardiovascular diseases are the main cause of death worldwide. The myocardial performance index (Tei index) is an accepted method for the evaluation of the systolic and diastolic function of the heart. There is not enough data about the association between the Tei index and the severity of unstable angina disease. In this study, we evaluated the association between the Tei index and unstable angina. Material and methods: The association between the Tei index measured by two different methods (tissue and continuous Doppler) and the severity of coronary artery disease in 170 adult patients was evaluated. The Tei index higher than 0.55 in tissue Doppler and 0.4 in continuous Doppler methods were considered as abnormal. Finally, the association between the Tei index and angiography findings was evaluated. Results: The mean age of patients was 58.26±10.62 years. The association between Tei index measured by the two methods mentioned above and the severity of coronary artery disease was not significant statistically. (p value=0.67 and 0.072 respectively) Conclusion: there is no association between the severity of coronary artery disease (1-3 vessel disease) and the Tei index in patients with unstable angina.